2013
DOI: 10.1016/j.anifeedsci.2013.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of essential oil combinations on sheep ruminal fermentation and digestibility of a diet with fumarate included

Abstract: a b s t r a c tFour Hu sheep (27.5 ± 2.6 kg body weight), fitted with ruminal and duodenal fistula, were used to investigate the effects of a mixture of essential oils (EO) or their active components on rumen fermentation, microbial population, and nutrient digestibility. Four treatments in 4 × 4 Latin square design were used: basal diet added with 25 g/day monosodium fumarate (Control); Control plus 1 g/day of EO combinations (EOC, mixture of equal ratio of oil from clove, oregano, cinnamon, and lemon); and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
42
2
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 42 publications
14
42
2
5
Order By: Relevance
“…Similar results were reported by Castillejos et al [43]. Instead, Patra and Yu [30] found that VFA concentration was affected only by oregano and clove EOs while the supplementation of EOs in sheep diets did not show any effect on VFA production [20,36]. Some researchers showed that some EOs have positive effects on VFA molar proportions by decreasing the acetate production and increasing propionate production [44][45][46].…”
Section: Effects On Production Of Volatile Fatty Acidssupporting
confidence: 68%
See 1 more Smart Citation
“…Similar results were reported by Castillejos et al [43]. Instead, Patra and Yu [30] found that VFA concentration was affected only by oregano and clove EOs while the supplementation of EOs in sheep diets did not show any effect on VFA production [20,36]. Some researchers showed that some EOs have positive effects on VFA molar proportions by decreasing the acetate production and increasing propionate production [44][45][46].…”
Section: Effects On Production Of Volatile Fatty Acidssupporting
confidence: 68%
“…In vitro NH3 concentration was also decreased by a combination of EOs composed of thyme, oregano, cinnamon and lemon applied at 0-0.5 g/L levels along with fumarate [35]. Lin et al [36] observed a NH3 inhibition with a mixture of EOs composed of clove, oregano, cinnamon and lemon in sheep (1 g/day). Contrasting results on in vivo NH3 production were found by Hristov et al [31] and Tekippe et al [32] by feeding dairy cows with a supplementation of oregano leaves.…”
Section: Controlmentioning
confidence: 97%
“…In vivo studies have been conducted to investigate the effect of EO on feed intake and ruminal and nutrient apparent digestibility, but results are inconsistent (Lin et al, 2013). Santos et al (2010) observed that supplementation of EO complex (eugenol, geranyl acetate and coriander oil) numerically reduced DMI in lactating dairy cow, which agrees with our result on sheep.…”
Section: In Vivo Experimentssupporting
confidence: 82%
“…Furthermore, if combining different EO components together can replace natural EOs as additive, existing problems on natural EO such as composition instability, difficulties in collection, and high cost, can be solved. Contrary to our finding regarded methane emission, Lin et al (2012Lin et al ( , 2013 found that a balanced combination of EO and EO active components (a mixture of thyme, oregano, cinnamon, and lemon essential oil at an equal ratio, and a mixture of eugenol, carvacrol, citral, and cinnamylaldehyde at an equal ratio) has greater methane reduction ability compared with other combinations. However, that EO are strong inhibitors of methanogenesis in the rumen could be attributed to different types and concentrations of secondary plant metabolites such as terpeniods and phenylpropanoids present in oils (Agarwal et al, 2009;Sallam et al, , 2012Soltan et al, 2011).…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation